Enabling knowledge sharing in a production context in China - Muniz, Jorge [UNESP]; Ribeiro, Vagner Batista [UNESP]; Hong, Jacky Fok Loi; Wintersberger, Daniel; Salomon, Valerio Antonio Pamplona [UNESP] (Wiley, 2024)
There is limited research on the cultural influence on knowledge sharing in production contexts. In view of the gap in literature, this study draws on a multi-criteria decision-making approach, the analytic hierarchy process (AHP), to identify and rank different enabling factors of knowledge sharing in the workplace of a Chinese electronics plant on the basis of the relative importance ascribed to them by operators, leaders, and managers. The fieldwork research was conducted in a Chinese electronic plant, considering the judgment of 121 operators (blue-collar workers), 56 production leaders, and 9 managers selected by convenience. The findings reinforce the understanding about the importance of integrating factors related to people, process, and knowledge to enable knowledge management in different cultural contexts, which may support managers' needs for lessons learned from other organizations in the areas of knowledge management, organizational learning, and process management.